2023
DOI: 10.1093/biolre/ioad031
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptomic response of bovine uterine tissue is altered in response to sperm from high- and low-fertility bulls

Abstract: Despite stringent quality control checks, some bulls with apparently normal semen quality yield lower than expected pregnancy rates. This study profiled the transcriptome and performed histological analysis of the bovine uterus in response to sperm from high fertility (HF) and low fertility (LF) bulls. Post-mortem uterine biopsies and uterine explants were collected from heifers 12 h after a fixed time artificial insemination (AI) to a synchronised oestrus with frozen–thawed semen from 5 HF (fertility rate 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The introduction of seminal plasma upregulates inflammatory mediators in the bovine endometrium [ 104 ] indicating that this is also an essential process required to protect the uterus and promote fertility. Male fertility can affect this response, with insemination by high-fertility bulls causing alterations in the transcriptomic response relative to these induced by low-fertility bulls, particularly with respect to immune system genes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of seminal plasma upregulates inflammatory mediators in the bovine endometrium [ 104 ] indicating that this is also an essential process required to protect the uterus and promote fertility. Male fertility can affect this response, with insemination by high-fertility bulls causing alterations in the transcriptomic response relative to these induced by low-fertility bulls, particularly with respect to immune system genes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, components of seminal plasma were shown to alter the endometrial transcriptome [ 36 ]. Artificial insemination of heifers with semen from low and high-fertility bulls led to differential gene expression, with high-fertility semen leading to increased expression of genes involved in immune response and inflammation [ 37 ]. Transcriptomic studies have also identified signalling molecules supporting embryonic development in the first seven days after ovulation [ 38 ].…”
Section: Introductionmentioning
confidence: 99%